The Paradox of Digital Electoral Governance: The Role of SILON-SIPOL-SIREKAP in Indonesia’s Electoral Accountability - Albahori Albahori; Sunarto Sunarto; Gatot Hery Djatmika; T. Herry Rachmatsyah (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines Indonesia's digital electoral governance systems—SILON, SIPOL, and SIREKAP—designed to uphold the constitutional principles of direct and fair elections (LUBER-JURDIL). SILON demonstrated an efficiency of 80% in processing candidate lists, achieving 30% compliance with female representation. SIPOL reduced administrative errors by 40%; however, systemic challenges remain. SIREKAP encountered a 12% discrepancy in vote recapitulation in rural areas such as Ogan Komering Ilir, mainly due to offline data entry bottlenecks (KPUD Sumsel, 2024). These issues illustrate Heeks' (2001) concept of the "design-reality gap," where failures arise not from technical inadequacies but from misalignments between digital systems and decentralized institutional contexts. SIPOL's dependence on manual submissions from 18 political parties resulted in delays, highlighting the phenomenon of "automation theater" (Warburton & Aspinall, 2019)—a superficial digitalization that obscures underlying bureaucratic inefficiencies. The contrast between urban and rural areas is significant. While SIREKAP's blockchain protocols ensured 89% transparency in urban precincts, they faltered in 31% of rural locations due to analog errors (KPU Technical Guideline No. 15/2023). In conservative regions such as Lahat, only 24% of candidate placements were female, despite SILON's gender quotas, indicating the presence of sociocultural barriers. The findings suggest the need for hybrid models that blend digital precision with grassroots engagement, as evidenced by KPUD Sumsel's literacy campaigns, which reduced SIREKAP discrepancies from 18% to 12%. Ensuring sustainable electoral integrity necessitates addressing institutional misalignments alongside technological advancements